Determination of alpha particles concentration in some soil samples and the extent of their impact on health - Thabayneh, Khalil M. (Penerbit Universiti Kebangsaan Malaysia, 2016)
The radon concentration, the exhalation rates and the radiation exposure from samples of soil collected from different sites at Hebron province in Palestine were measured using the sealed-can technique based on the CR-39 detectors. The total average values of radon concentrations for 0, 20, 40 and 60 cm depths were 294, 357, 433 and 512 Bqm−3, respectively. As expected, our data showed an increase of radon concentration levels with depth. The average values of surface exhalation rates, the effective dose equivalent (Ep), the annual effective dose (HE), the dissolved in soft tissues (Dsoft, tissue) and the dose rate due to alpha-radiation in lung (Dlung) were calculated. The values were found to be within the safe limits as recommended by ICRP and WHO. The results showed that these areas are safe from the health hazard site of view as far as the radon is concerned.